The (ya)illi Relative Clause in Levantine Arabic: A Case for Head -External Structure - Abu Helal, Abdel-Rahman (Dirasat: Human and Social Sciences, 2021)
In this article, we present an argument based on empirical evidence from Levantine Arabic in favor of the fact that the (ya)illi relative clause (YRC) has a head-external structure (e.g., a matching). A set of state-of-the-art diagnoses that speak against the head NP raising in YRCs is fully demonstrated and analyzed in the context of some grammatical structures. As confirmed by the evidence, if the possibility of raising syntax in YRCs is ruled out in such restricted contexts, it follows that some variant of head external analysis for the YRC is in order; at least as another structure that characterizes this type of relative clauses in addition to head NP raising structure that was approved in the representative literature such as Ouhalla (2004) and Aoun, Benmamoun and Choueiri (2010).